Dr No - Fleming, Ian (London Pan Books, 1970)
British secret agent James Bond investigates the mysterious disappearance of an MI6 station chief in Jamaica, with the evidence pointing to the reclusive Dr. Julius No. Discovering the alluring Honeychile Rider, Bond runs afoul of the doctor's "no trespassing" policy and must survive a sadistic obstacle course.
English Fiction.
Keywords: Bond, James (Fictitious character) -- Great Britain -- Intelligence service